Cover Image. (14th September 2021) - Zhao, Yunxia; Zhang, Jihong; Qu, Dapeng; Yang, Yanyun; Wu, Wenguang; Sun, Ke; Liu, Yi
Abstract : The cover image is based on the Original Article Benthic environmental impact of deep sea cage and traditional cage fish mariculture in Yellow Sea, China by Jihong Zhang et al., https://doi.org/10.1111/are.15374 .